Race: a tool of power in the construction of identities, and the thought of Geraldo Rocha - Borges, Erica Naiara Ribeiro (2020)
This article analyzes race and miscegenation in the construction of post-colonial identity in Brazil as a tool of power to justify the subordination and erasure of blacks and mestizos in the formation of society. We insert the thought of Geraldo Rocha, who understands that the mestizo from the backlands is an example of the authentic national identity. Through bibliographic review, we analyzed this process of positivating a mestizo and the theoretical influences that allowed this positivation.